Synthesis of CdS sensitized TiO2 photocatalysts: methylene blue adsorption and enhanced photocatalytic activities - Makama, Abdullahi B.; Ali, Salmiaton; Saion, Elias; Choong, Thomas Shean Yaw; Abdullah, Norhafizah (Hindawi Publishing Corporation, 2016)
A series of CdS/ nanocomposites with different Cd to Ti molar ratio were synthesized from P25- nanopowder using microwave-assisted hydrothermal method. The as-produced powders were characterized by XRD, electron microscopy, EDX, and UV-Vis diffuse reflectance spectroscopy. The adsorption capacity and photocatalytic activity of the samples were investigated using methylene blue as a model pollutant. Sorption tests revealed that the adsorption of MB onto the samples obeys the Freundlich-Langmuir isotherm model. The sorption capacity decreased as follows: . The results of the photocatalytic tests under high-intensity discharge (HID) lamp revealed that CdS/ powders with low Cd to Ti molar ratios exhibited much higher activities than P25-. The CdS/ sample with 20% CdS/(TCd2) showed the most activity among all these samples. The results also show that the Cd to Ti molar ratio of the nanocomposite has a significant effect on the photodegradation of MB and the enhanced activities exhibited by the nanocomposites are because of the low rate of electron-hole recombination.